2012
DOI: 10.1080/13691058.2012.673639
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care for gay, lesbian, bisexual and transgender people

Abstract: There is little understanding in Australia of the particular issues faced by gay, lesbian, bisexual and transgender (GLBT) people in end-of-life care and advance care planning. This exploratory qualitative study aimed to achieve an initial understanding of these issues to compare with the international literature and inform the development of a larger study involving GLBT consumers. Consultations were carried out with 19 service providers and 6 GLBT community members located in the Northern Rivers and metropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 25 publications
1
66
0
Order By: Relevance
“…7-10 Further, we observed that trans-aging is still most likely to be lumped together with LGB aging. [11][12][13][14][15][16][17] We also found a small international literature on the transgender population. [18][19][20][21][22] However, the international literature on trans-aging appears to be extremely sparse.…”
Section: Literature Search Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…7-10 Further, we observed that trans-aging is still most likely to be lumped together with LGB aging. [11][12][13][14][15][16][17] We also found a small international literature on the transgender population. [18][19][20][21][22] However, the international literature on trans-aging appears to be extremely sparse.…”
Section: Literature Search Findingsmentioning
confidence: 97%
“…11,[41][42][43] Witten 44 examines the challenges at later-life and end-of-life stages. However, only anecdotal data are provided.…”
Section: Lack Of Services/social Supportmentioning
confidence: 99%
“…Even less is known about the experiences of older transgender or intersex individuals, as they get older and face the loss of their partners (Witten & Eyler, 2012). Recent explorative research in Australia suggests that LGBT individuals face barriers in accessing appropriate end-of-life care due to discrimination and lack of knowledge about LGBT needs and experiences (Cartwright, Hughes, & Lienert, 2012). Research exploring the needs of older lesbians and gay men highlights concerns about the experience of loss of a partner, and the lack of appropriate bereavement support available (Gay and Grey in Dorset, 2006;Smith, McCaslin, Chang, Martinez, & McGrew, 2010).…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, there is a lack of understanding of what these initiatives have meant for older lesbian and gay people in terms of their expectations for and experiences of aged‐care, and whether all people have been able to benefit from these initiatives. Studies conducted in Australia have examined experiences and perceptions of residential‐care, which broadly show a range of concerns and fears, including management of identity disclosure, lack of safe spaces for intimate relationships and the need for culturally safe and inclusive services (Barrett, ; Barrett, Crameri, Lambourne, Latham, & Whyte, ; Cartwright, Hughes, & Lienert, ; Chamberlain & Robinson, ; Crameri, Barrett, Latham, & Whyte, ; Harrison, ; Hughes, , ; Lovelock, ; Waite, ). Research has also found lesbian and gay people tend to have low awareness regarding their legal options, with most avoiding or not being given the opportunity to discuss the issue with healthcare providers (Hughes & Cartwright, , ).…”
Section: Introductionmentioning
confidence: 99%